2018
DOI: 10.1152/japplphysiol.00889.2017
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit territories in human genioglossus estimated with multichannel intramuscular electrodes

Abstract: The discharge patterns of genioglossus motor units during breathing have been well-characterized in previous studies, but their localization and territories are not known. In this study, we used two newly developed intramuscular multichannel electrodes to estimate the territories of genioglossus motor units in the anterior and posterior regions of the muscle. Seven healthy men participated. Each electrode contained fifteen bipolar channels, separated by 1 mm, and was inserted percutaneously below the chin, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
0
21
1
Order By: Relevance
“…This compartmentalisation of the genioglossus has been supported by evidence of regional variation in neural drive in awake healthy adults during breathing (Vranish & Bailey, 2015;Luu et al 2018). Luu et al (2018) showed that peak inspiratory motor unit activity predominantly occurs in the posterior region of the genioglossus, although only a few inspiratory units were recorded. Vranish & Bailey (2015) reported a larger electromyographic signal (EMG) in the posterior muscle regions than the anterior compartments without differential activation between the regions.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…This compartmentalisation of the genioglossus has been supported by evidence of regional variation in neural drive in awake healthy adults during breathing (Vranish & Bailey, 2015;Luu et al 2018). Luu et al (2018) showed that peak inspiratory motor unit activity predominantly occurs in the posterior region of the genioglossus, although only a few inspiratory units were recorded. Vranish & Bailey (2015) reported a larger electromyographic signal (EMG) in the posterior muscle regions than the anterior compartments without differential activation between the regions.…”
Section: Introductionmentioning
confidence: 80%
“…Morphologically, these compartments have muscle fascicles that course posteriorly from their insertion into the mandible either horizontally or fan out obliquely (Sanders & Mu, 2013), and we adopt this terminology in our study. Furthermore, the posterior and anterior compartments of the genioglossus are also innervated by different branches of the hypoglossal nerve (Mu & Sanders, 2010) and they may be composed of muscle fibres arranged in series (Sanders & Mu, 2013;Luu et al 2018). This compartmentalisation of the genioglossus has been supported by evidence of regional variation in neural drive in awake healthy adults during breathing (Vranish & Bailey, 2015;Luu et al 2018).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…human muscles. Héroux et al (2015) and Luu et al (2018) showed a mostly uniform distribution of muscle fibres belonging to a MU in the medial gastrocnemius and in the genioglossus, respectively. The defined MU territories we observed in the human longissimus pars lumborum are in line with findings in the cat where stimulation of a nerve branch innervating the longissimus generated a localized action potential spanning mainly adjacent segments (Wada et al 2003;Durbaba et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…MUs with a minimum of 300 action potentials during the lumbar isometric contractions were considered to compute spike-triggered averages in the fine-wire multi-unit EMG (Farina et al 2008;Héroux et al 2015). We determined the spatial localization of a single MU by evaluating the fine-wire recording sites where the spike-triggered fine-wire EMG average crossed a threshold value of ±4 standard deviations (SD) of the baseline activity computed in a 25 ms window (−35 ms to −10 ms) prior to the target MU spike time (Héroux et al 2015;Luu et al 2018) (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%